Refeeding partially reverses impaired fracture callus in undernourished rats - Botega, Iara I.; Guedes, Patrícia M. S. G.; Ximenez, João Paulo B.; Zamarioli, Ariane; Volpon, José B. (Frontiers in Endocrinology, 2024)
Given the relation between food restriction and compromised bone quality (3,(7)(8)(9)(10)(11), 26 associated with the crucial role of a healthy bone microenvironment in proper fracture 27 healing, it is not surprising that undernutrition may lead to an impaired bone repair, resulting 28 in lower-quality bone callus. Numerous studies have investigated the effects of nutrient 29 restrictions on bone health, examining the depletion of macronutrients (such as proteins or 30 phosphate) or specific micronutrients (such as calcium or vitamin D) (9,(12)(13)(14)(15)(16)(17)(18)(19)(20). However, it 31 is worth noting that undernutrition in clinical settings often involves limited food intake, 32 leading to the restriction of multiple nutrients, and it may be better represented by a general 33 food restriction model.